Ophthalmomyiasis Externa Caused by Oestrus ovis - Shankar, Mahesh Kumar; Diddapur, Seethalakshmi Krishnamurthy; Nadagir, Shobha Dhruv; Kota, Subramanya Giliyar (Journal of Laboratory Physicians, 2012)
A 50-year-old male presented with foreign body sensation, pain, and redness in left eye. Slit-lamp biomicroscopy revealed tiny larvae crawling around the conjunctival sac. The larvae, numbering 13, were mechanically removed under topical anesthesia and identified under light microscope as first-stage larvae of Oestrus ovis causing ophthalmomyiasis externa.
Keywords: Oestrus ovis; larvae; ophthalmomyiasis externa